Penerapan Manajemen Risiko pada Proses Pengembangan Perangkat Lunak - Setiawan, Aji Awang; Kharisma, Dede; Sophia, Aya (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
The software developing process is a very complex process, because it includes department, company, and individual which have different knowledge and specialization. Additionally, the demand to distribute the software on time and minimum cost, and the extreme competition between the software developers causing new problems and uncertainty. Therefore, the software developing project rely on the adequate project management to achieve the best result to fulfill the previously set parameters of time efficiency, cost, and quality. At a glace, the risk management perhaps increase the complexity of the process itself, but the fact it can reduce the risk and complexity of this software developing project. This journal applies literature review method, and the data are from the research results published in the national and international online journals, and books review the risk management of software developing project. The writer’s research results bring out that the risk factors are found in the software developing process, including the project documentation risk, communication, human resources, culture, bug severity level, and bug repair priority level.